Comparing student's perceptions of blended learning and traditional classroom deliveries in an english professional communication course in a technical university - Kalthom, Husain; Aida Nasirah, Abdullah; Norasiken, Bakar; Faaizah, Shahbodin; Norshaidatul Hasana, Ishak; Hazmilah, Hasan (2011)
An interview was conducted to under graduates of Bachelor of Computer Engineering and Electronic who were sat for English Professional Communication course at Universiti Teknikal Malaysia Melaka (UTeM) in Malaysia. This study compares students' perceptions of the overall satisfaction of the course and the delive1ies methods. One group of students were kept in a traditional in-class section, and another group in a blended-learning section in which the primary course delive1y method was partly online, whereby students met in class on a limited number of occasions. Overall perceptions of the course, lecturer/instructor and learning outcomes were positive for both groups. Students depicted strong inclination that they would use the material in their careers. The majority of students in the blended learning section indicated that they would take another elective course using blended learning approach if it were offered. However, some interesting differences were noted. Specifically, students in the traditional setting were more satisfied with the clarity of instruction. Blended-learning students also indicated fitmly that their analytical skills improved as a result of the course. The results suggest that the two delive1y methods were similar in terms of final learning outcomes.